2005
DOI: 10.1093/her/cyh045
|View full text |Cite
|
Sign up to set email alerts
|

Are anti-smoking parenting practices related to adolescent smoking cognitions and behavior?

Abstract: The aim of this study was to explain the effects of anti-smoking parenting practices on adolescent smoking cognitions and behavior by showing the mediating effects of cognitions. Data were gathered among Dutch high school students in the control condition of the European Smoking prevention Framework Approach (ESFA). Anti-smoking parenting practices were measured by parental reactions to smoking, house rules, and frequency and content of communication about smoking. Attitudes, perceived social influences and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 34 publications
10
80
0
1
Order By: Relevance
“…When parents only talk to their children about rules and tell them not to use substances, adolescents feel threatened and report increased rates of alcohol, tobacco and drug use (Chaplin et al, 2014;Huver et al, 2006;Kam, 2011), although in one study the results were positive but not statistically significant (Nonnemaker et al, 2012). In a qualitative study, adolescents reported that when their parents use such communication, they tend to ignore what is said (Maggi et al, 2014).…”
Section: Harder Vs Softer Communicationmentioning
confidence: 96%
See 4 more Smart Citations
“…When parents only talk to their children about rules and tell them not to use substances, adolescents feel threatened and report increased rates of alcohol, tobacco and drug use (Chaplin et al, 2014;Huver et al, 2006;Kam, 2011), although in one study the results were positive but not statistically significant (Nonnemaker et al, 2012). In a qualitative study, adolescents reported that when their parents use such communication, they tend to ignore what is said (Maggi et al, 2014).…”
Section: Harder Vs Softer Communicationmentioning
confidence: 96%
“…Softer communication, however, is viewed more positively (Guilamo-Ramos et al, 2008;Kulbok et al, 2010;Maggi et al, 2014). When parents include messages about health risks and potential consequences of use, adolescents are less likely to use substances (Chaplin et al, 2014;Huver et al, 2006). However, in one study, discussion of consequences had no effect on alcohol use (Reimuller, Hussong, & Ennett, 2013) and in another had a detrimental effect on cannabis use initiation (Nonnemaker et al, 2012).…”
Section: Harder Vs Softer Communicationmentioning
confidence: 96%
See 3 more Smart Citations